Pengaruh Penguasaan Kosakata dan Minat Baca terhadap Kemampuan Menulis Teks Deskriptif Siswa - Melinda Sariningsih (Universitas Indraprasta PGRI, 2021)
This research is a qualitative research on Indonesian language education, especially on the influence of vocabulary mastery and reading interest on the ability to write descriptive texts. This study aims to determine the effect of vocabulary mastery and reading interest together on the ability to write descriptive texts of State Vocational High School students in Kebumen Regency. In addition, it also aims to determine the effect of vocabulary mastery on the ability to write descriptive texts of State Teacher High School students in Kebumen Regency. The next objective was to determine the effect of reading interest on the ability to write descriptive texts of State Vocational High School students in Kebumen Regency. The method used in this study is a survey method with multiple linear regression correlational approach with a sample of 65 students. The results showed: There is a significant effect of vocabulary mastery and reading interest on the ability to write descriptive texts at the State Teacher Training School in Kebumen Regency. This can be seen from the results of statistical calculations carried out and analyzed in this study. From the description of the data after the correlation analysis, the correlation coefficient is 42.7% and the determination coefficient is 40.8%. After testing with the SPSS program, it is proven that the correlation coefficient is significant. This means that there is an effect of vocabulary mastery and reading interest together on the ability to write descriptive text.Keywords: Vocabulary mastery, reading interest, ability to write descriptive text.